The myth of Gorgo/Medusa in ancient written sources - Anna Lazarou (Proceedings (European Academy of Sciences and Arts))
The present article reports all ancient writers and poets who dealt with the Gorgoneian head and the Gorgon-Medusa related myth presented in a chronological order basically during the 1st millennium B.C. from Homeric epics to late antiquity of Fabius Planciades Fulgentius and Ioannis Malalas in the 5th and 6th c. A.D. Essentially it is a discussion on the ancient written sources, based on the original texts. Especially for the most ancient sources - such as Homer, Hesiod, Cyclic epics – and references were made to known scholars in the field of philology. Particularly critical discussion and comments are made, along with the investigation of the primary ancient writing sources, as well as the related iconography. The final conclusions show the degree of influence of ancient written sources on art, but also vice versa, that is, how much art influenced ancient texts.